Transformational Leadership Model of Muhammadiyah Branch Leaders in Bandung Regency - Erawan, Jamjam; Azis, Yaya Abdul; Satibi, Iwan (Jurnal Studi Ilmu Pemerintahan, 2023)
Leadership factors determine the development of Muhammadiyah. This leadership includes central, district, regional, branch, and branch levels. This research's problem lies with the department head, especially in Bandung Regency. The theory used in this study is the leadership theory from Avolio, which states that the transformational leadership model contains four components: Idealized Influence, Inspirational Motivation, Intellectual stimulation, and Individualized Consideration. The method used is a descriptive method with a qualitative approach. Data collection techniques perform using literature study, observation, and interviews. Informant determination is doing with purposively. The study results show that the Muhammadiyah Regional Leadership in Bandung Regency has quite an excellent Idealized Influence with a clear vision, mission, and program. However, Inspirational Motivation among branch leaders shows high motivation by encouraging and encouraging subordinates. On the other hand, regional and branch leaders have shown intellectual stimulation to their members to promote their academic level. The attention given by regional and branch leaders can show Individualized Consideration as a mentor.